Development of an Inflammatory CD14+ Dendritic Cell Subset in Humanized Mice - Iwabuchi, Ryutaro; Ide, Keigo; Terahara, Kazutaka; Wagatsuma, Ryota; Iwaki, Rieko; Matsunaga, Hiroko; Tsunetsugu-Yokota, Yasuko; Takeyama, Haruko; Takahashi, Yoshimasa (Frontiers in immunology, 2021)
Humanized mouse models are attractive experimental models for analyzing the development and functions of human dendritic cells (DCs) in vivo . Although various types of DC subsets, including DC type 3 (DC3s), have been identified in humans, it remains unclear whether humanized mice can reproduce heterogeneous DC subsets. CD14, classically known as a monocyte/macrophage marker, is reported as an indicator of DC3s. We previously observed that some CD14 + myeloid cells expressed CD1c, a pan marker for bona fide conventional DC2 (cDC2s), in humanized mouse models in which human FLT3L and GM-CSF genes were transiently expressed using in vivo transfection (IVT). Here, we aimed to elucidate the identity of CD14 + CD1c + DC-like cells in humanized mouse models. We found that CD14 + CD1c + cells were phenotypically different from cDC2s; CD14 + CD1c + cells expressed CD163 but not CD5, whereas cDC2s expressed CD5 but not CD163. Furthermore, CD14 + CD1c + cells primed and polarized naïve CD4 + T cells toward IFN-γ + Th1 cells more profoundly than cDC2s. Transcriptional analysis revealed that CD14 + CD1c + cells expressed several DC3-specific transcripts, such as CD163, S100A8, and S100A9, and were clearly segregated from cDC2s and monocytes. When lipopolysaccharide was administered to the humanized mice, the frequency of CD14 + CD1c + cells producing IL-6 and TNF-α was elevated, indicating a pro-inflammatory signature. Thus, humanized mice are able to sustain development of functional CD14 + CD1c + DCs, which are equivalent to DC3 subset observed in humans, and they could be useful for analyzing the development and function of DC3s in vivo .